Technical Advance: Fluorescent reporter reveals insights into eomesodermin biology in cytotoxic lymphocytes. Issue 2 (1st February 2013) - Paley, Michael A.; Gordon, Scott M.; Bikoff, Elizabeth K.; Robertson, Elizabeth J.; Wherry, E. John; Reiner, Steven L.
Abstract : Fluorescent reporter allele provides insights on the role for eomesodermin in NK development, CD8 + T cell effector function, and central memory formation. Abstract : The T‐box transcription factor Eomes is expressed in cytotoxic immune cells and plays an important role in development, maintenance, and function of these cell types. Identification and separation of cells with differential Eomes expression would allow for better understanding of the transcriptional program governing these cytotoxic lymphocytes. Here, we report the use of an Eomes gfp ‐targeted mouse allele that displays robust fidelity to Eomes protein expression in NK and T cells. Use of this reporter mouse revealed that Eomes expression in antiviral effector cells did not correlate with enhanced cytotoxicity but rather was associated with more efficient central memory differentiation. Weakening of reporter activity in Eomes‐deficient CD8 + T cells revealed a critical role for Eomes protein in maintaining central memory cells that have activated the Eomes locus. Characterization of reporter activity in NK lineage cells also permitted identification of a novel intermediate of NK cell maturation. Thus, the murine Eomes gfp ‐targeted allele provides a novel opportunity to explore Eomes biology in cytotoxic lymphocytes.